Nursing Implementation of Nutritional Management in Diarrhoea Children with Nutritional Deficit Problems - Jawiah; Yunike; Febriyanti, Dita (Yayasan Rumah Ilmu Professor, 2023)
Based on medical record data from Siti Fatimah Hospital Palembang, children aged 6-12 years who suffered from diarrhoeal diseases in 2019 to 2021 were 28 patients. Diarrhoea in children must be treated immediately because diarrhoea that is too frequent in children can cause disruption of the gastrointestinal system such as malabsorption which can cause children to enter less nutrients into the body and can cause nutritional deficits in children with diarrhoea. Methods: This type of research design uses a descriptive design in the form of a case study. The approach used is a nursing care approach which includes assessment, nursing diagnosis, planning, implementation, evaluation and documentation. The case study subjects were 2 pediatric patients suffering from diarrhoea, patient 1 aged 6 years and patient 2 aged 7 years who had nutritional deficit nursing problems. This research was conducted at Siti Fatimah Hospital Palembang in 2022. Results: Implementation of nutrition management nursing is effective to overcome the problem of nutritional deficits that occur in children with diarrhoea by showing the results of weight gain in children every day during the nursing process. Discussion: It is hoped that the patient's parents can recognise the signs of diarrhoea in children so that nutritional deficiencies do not occur and it is hoped that parents can apply the nutritional management that the author has taught.